2023
DOI: 10.3389/fphys.2023.1083240
|View full text |Cite
|
Sign up to set email alerts
|

A molecular perspective on the invasibility of the southern ocean benthos: The impact of hypoxia and temperature on gene expression in South American and Antarctic Aequiyoldia bivalves

Abstract: When an organism makes a long-distance transition to a new habitat, the associated environmental change is often marked and requires physiological plasticity of larvae, juveniles, or other migrant stages. Exposing shallow-water marine bivalves (Aequiyoldia cf. eightsii) from southern South America (SSA) and the West Antarctic Peninsula (WAP) to changes in temperature and oxygen availability, we investigated changes in gene expression in a simulated colonization experiment of the shores of a new continent after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…This wide distribution range on both sides of the Drake Passage has given rise to several revisions of its taxonomic status [ 25 ]. Recently, Muñoz-Ramírez et al [ 26 ] highlighted the role of the Antarctic circumpolar current as a biogeographic barrier between the Antarctic Peninsula and South America, confirming the existence of two different species across the Drake Passage, which, according to Martínez et al [ 27 ], have different levels of susceptibility to two major climate change stressors, namely, temperature shifts and hypoxia. González-Wevar et al [ 28 ] suggested the presence of several cryptic species comprising two lineages along the Antarctic Peninsula (5.78% COI p-distance), a third linage in South America (6.5–7.5% COI and 1.2% ITS p-distances) with respect to the Antarctic peninsula, and two additional mitochondrial lineages on Kerguelen Island and the Falkland/Malvinas Islands.…”
Section: Introductionmentioning
confidence: 98%
“…This wide distribution range on both sides of the Drake Passage has given rise to several revisions of its taxonomic status [ 25 ]. Recently, Muñoz-Ramírez et al [ 26 ] highlighted the role of the Antarctic circumpolar current as a biogeographic barrier between the Antarctic Peninsula and South America, confirming the existence of two different species across the Drake Passage, which, according to Martínez et al [ 27 ], have different levels of susceptibility to two major climate change stressors, namely, temperature shifts and hypoxia. González-Wevar et al [ 28 ] suggested the presence of several cryptic species comprising two lineages along the Antarctic Peninsula (5.78% COI p-distance), a third linage in South America (6.5–7.5% COI and 1.2% ITS p-distances) with respect to the Antarctic peninsula, and two additional mitochondrial lineages on Kerguelen Island and the Falkland/Malvinas Islands.…”
Section: Introductionmentioning
confidence: 98%
“…As environmental conditions continue to change, marine species must adapt and potentially shift their distributions to areas with more suitable conditions for their survival and reproduction 1,[5][6][7][8][9][10][11] . Therefore, understanding the present spatio-temporal distribution of marine species and accurately predicting their future is a critical challenge in the current context of global warming 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…These approaches provide a broader perspective by focusing on large-scale patterns and processes, allowing for the prediction of species distribution and abundance at regional and global scales 22 . Therefore, this global perspective is essential for the evaluation of climate change and biodiversity 12,13,23 . The results of large-scale predictions can contribute to the development of effective management strategies with global policy objectives, enabling decision-makers to prioritize conservation efforts, implement sustainable practices, and mitigate the impacts of climate change on marine ecosystems 14,24 .…”
Section: Introductionmentioning
confidence: 99%